Expression of DNA repair genes in oral squamous cell carcinoma using reverse transcription-quantitative polymerase chain reaction - Oliveira Alves, Mônica Ghislaine; da Silva Miguel, Natália; Ferreira, Camila Cristina Panisello [UNESP]; Alvarenga, Elis Ribeiro; Tonon, Bruna Manzanares; de Barros, Patrícia Pimentel [UNESP]; Carta, Celina Faig Lima [UNESP]; Paschoal, Maria Beatriz Nogueira; de Sales Chagas, José Francisco; Bandeira, Celso Muller [UNESP]; Nunes, Fábio Daumas; Almeida, Janete Dias [UNESP] (Elsevier, 2020)
Objective: The aim of this study was to evaluate the expression of DNA repair genes in cases of oral squamous cell carcinoma (OSCC). Study Design: Expression of the MLH1, MSH2, MLH3, ATM, MRE11A, XRCC1, and PMS2 genes was evaluated by reverse transcription–quantitative polymerase chain reaction in the OSCC group (32 patients) and the control group (15 patients). The groups were compared by using the Mann-Whitney test, with Bonferroni correction. Associations between gene expression levels and clinical data were explored by using Pearson's and Spearman's correlation coefficients, with P value less than. 05 indicating a significant difference. Results: The MLH1, MSH2, MLH3, ATM, MRE11A, XRCC1, and PMS2 genes were downregulated in the OSCC group compared with the control group, with significant values for MLH1 (P < .0001); MSH2 (P = .038); MLH3 (P < .0001); ATM (P < .0001); MRE11A (P < .0001); XRCC1 (P = .0004); and PMS2 (P = .008). Analysis of the correlation between gene expression and clinical data only revealed a significant negative correlation between age and expression of the PMS2 gene. Conclusions: Expression of the DNA repair genes MLH1, MSH2, MLH3, ATM, MRE11 AMRE11A, XRCC1, and PMS2 was reduced in OSCC.